Reckoning with the Communist Past in Poland Thirty Years After the Regime Change in the Light of the European Convention on Human Rights (Polish Yearbook of International Law, 2021)
The article discusses the point of interconnection between historical policy and international human rights law standards on the example of a so-called decommunisation Act enacted in Poland in 2016 that reduces retirement pensions and other benefits to individuals who were employed or in service in selected state formations and institutions in 1944-1990, amending the Act adopted in 2009. The Act of 16 December 2016 is analyzed in the light of the standards of the European Convention on Human Rights (ECHR), including relevant standards on coming to terms with the past as an element of transitional justice. The examination concludes that there is a discrepancy between the rationale for adopting this legislation in Poland, namely to reckon with the communist past and as such increase social trust in state institutions, and the legal solutions contained in the 2016 Act.